Editorial for Special Issue “Dynamics and Mechanics in Two-Dimensional Nanostructures: Simulation and Computation” - Kai Ren; Bin Ding; Gang Zhang (Nanomaterials, 2023)
Two-dimensional (2D) materials have completely different thermal transport characteristics from bulk materials [...]